Essential Role of the Interstitial Cells of Cajal in Nitric Oxide-Mediated Relaxation of Longitudinal Muscle of the Mouse Ileum - Tadayoshi Takeuchi; Kaori Fujinami; Akikazu Fujita; Yutaka Okishio; Tadashi Takewaki; Fumiaki Hata (Elsevier, 2004)
The role of interstitial cells of Cajal (ICC) in electrical field stimulation (EFS)-induced neurogenic responses in ileum was studied by using the ICC-deficient mutant (SLC-W/WV) mouse and its wild type. In the immunohistochemical study with anti-c-Kit antibody, ICC was observed in the myenteric plexus (MY) and deep muscular plexus (DMP) region in the wild type. In the mutant, ICC-MY were lost, only ICC-DMP were present. EFS induced a rapid contraction of the ileal segments from the wild type mouse in the direction of longitudinal muscle. In the mutant mouse, onset of contraction was delayed and its rate was slowed. EFS induced nonadrenergic, noncholinergic (NANC) relaxation in the presence of atropine and guanethidine in the wild type. A nitric oxide synthase inhibitor inhibited the relaxation and L-arginine reversed it. In the mutant, EFS did not induce NANC relaxation. There was no difference between the responsiveness of the segments from wild type and mutant mice to exogenously added acetylcholine or Nor-1. Taking into account the selective loss of ICC-MY in the mutant mice, it seems likely that ICC-MY have an essential role in inducing nitric oxide-mediated relaxation of longitudinal muscle of the mouse ileum and that ICC-MY partly participate in EFS-induced contraction. Keywords:: interstitial cells of Cajal (ICC), ICC-deficient mouse, longitudinal muscle, nitric oxide-mediated relaxation, acetylcholine-mediated contraction